STRUKTUR DAN UKURAN LAYAK TANGKAP UDANG JERBUNG (Penaeus merguiensis) DI PERAIRAN MENDAHARA ILIR - Dea Tri Ananda; Depison Depison; Lisna Lisna; Nelwida Nelwida; Muhammad Hariski (JURNAL PERIKANAN DAN KELAUTAN, 2023)
Mendahara Ilir area is one of the areas in East Tanjung Jabung which has a high enough potential for shrimp, one of which has high economic value is Jerbung Shrimp. It is feared that the increasing activity of catching Jerbung shrimp will lead to overfishing. One of the important things in catching fish is paying attention to the size structure of the caught shrimp. The size of shrimp suitable for capture is a reference in the management of capture fisheries for the sustainability of shrimp resources in the future. This study aims to determine the structure and size suitable for catching Jerbung shrimp using Sondong fishing gear in Mendahara Ilir waters. This study used the Simple Random Sampling method, that is, the number of samples taken was 10% of the total catch of Jerbung prawns. The results showed that Jerbung prawns caught using Sondong fishing gear were in the range of 100-156 mm. The coefficient value of the correlation between length and weight of Jerbung prawns is 2.3 which indicates that the growth pattern of Jerbung prawns is negative allometric. The percentage of suitable size for catching is 78% and not suitable for catching is 22%. The conclusion of this study is that the percentage of Jerbung shrimp size suitable for catching is greater than not suitable for catching but in this study it has not been included in the good criteria.